Managing Clopidogrel Resistance in Neurointervention: Surveying Current Approaches - Hyun Woo Kim; Ivo Bach; Juan Carlos Martinez Gutierrez; Adam A. Dmytriw; Salvatore D'Amato; Hussein A. Zeineddine; Albert J. Yoo; Sunil A. Sheth (Stroke: Vascular and Interventional Neurology)
Background Because of the variability in patient responses to clopidogrel and to reduce the risk of thromboembolic complications, adjusting the antiplatelet regimen based on platelet function testing has become a widespread practice in neurointervention. We aimed to explore current patterns related to this practice. Methods We conducted a survey targeting neurointerventionalists, comprising multiple‐choice questions and opportunities for free‐text responses when necessary. The survey was distributed via a professional society distribution list (the Society of Vascular and Interventional Neurology) and 2 consortium emailing lists (WovenEndoBridge and Neurointerventional Research Consortia). The data obtained from the responses were analyzed using descriptive statistics. Results A total of 133 neurointerventionalists, representing 79 institutions within 27 countries, responded to the survey. A total of 62% of respondents tested for clopidogrel resistance before any neurovascular stent placements. A total of 80% used VerifyNow point‐of‐care P2Y12 assay; other assays included multiplate analyzer, platelet function analyzer, and CYP2C19 genotype assay. Respondents reported 25 different therapeutic thresholds, with the P2Y12 reaction unit range between 60 and 180 most commonly used (16.4%). A total of 61% reported they would switch to ticagrelor in the case of persistent resistance. On the other hand, when patients are supratherapeutic, 48% did not make any changes, whereas 42% reduced clopidogrel dose. Finally, 93% opined that a well‐established protocol for management of clopidogrel resistance was needed. Conclusions Neurointerventional practice patterns around clopidogrel resistance remain heterogeneous. Our results underscore the need for evidence‐based guidance on the management of clopidogrel resistance in neurointervention.